Can Task Specificity Impact tDCS-Linked to Dual Task Training Gains in Parkinson's Disease? A Protocol for a Randomized Controlled Trial - Costa-Ribeiro, Adriana; Andrade, Suellen Mary Marinho dos Santos; Férrer, Mayane Laís Veloso; Silva, Ozair Argentille Pereira Da; Salvador, Maiara Llarena Silva; Smaili, Suhaila; Lindquist, Ana Raquel Rodrigues (Frontiers in Aging Neuroscience, 2021)
Patients with Parkinson’s disease (PD) have difficulties while performing dual-task activities, a condition present in everyday life. It is possible that strategies such as transcranial Direct Current Stimulation (tDCS) can be associated with motor training enriched with dual-task training to improve the performance of two concurrent tasks. Currently, it is unclear whether specific tasks and clinical conditions of PD patients have different results after the intervention. Therefore, the proposed randomized controlled trial will examine task-dependency in enhancing the effects of tDCS-linked rehabilitation training on PD and the relationships between baseline outcomes in responders and non-responders to therapy. Fifty-six patients with Parkinson’s disease will be recruited to participate in this sham-controlled, double-blind randomized multicentric clinical trial. Patients in modified Hoehn & Yahr stage 1.5 to 3, age between 40 and 70 years will be included. Subjects will be randomly assigned to an experimental group (EG) and a control group (CG). The EG will perform treadmill gait training associated with dual task exercises+tDCS, while the CG will only engage in treadmill gait training+tDCS. Blinded testers will assess patients before and after 12 intervention sessions and after a 4-week follow-up period. All patients will undergo a screening and an initial visit before being assessed for primary and secondary outcomes. The primary outcome measure is functional mobility measured by Timed Up and Go Test. Secondary outcomes include cognitive function, participation, motor function and body function and structure. This study will evaluate the effectiveness of an intervention protocol with tDCS, dual-task training and gait training in patients with PD. The study will also highlight the clinical factors and variability between individuals that could interfere in the training of a specific task and influence the therapeutic effect. Clinical Trial registration: www.ClinicalTrials.gov, identifier NCT04581590.